Tính : \(1\frac{1\frac{1\frac{...}{3}}{2}}{1\frac{2}{1\frac{3}{...}}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
giải:
ta có :
\(\frac{1+\frac{1}{2}+\frac{1}{3}+\frac{1}{4}}{1-\frac{1}{2}+\frac{1}{3}-\frac{1}{4}}:\frac{3+\frac{3}{2}+\frac{3}{3}+\frac{3}{4}}{2-\frac{2}{2}+\frac{2}{3}-\frac{2}{4}}\)
\(\frac{1+\frac{1}{2}+\frac{1}{3}+\frac{1}{4}}{1-\frac{1}{2}+\frac{1}{3}-\frac{1}{4}}.\frac{2\left(1-\frac{1}{2}+\frac{1}{3}-\frac{1}{4}\right)}{3\left(1+\frac{1}{2}+\frac{1}{3}+\frac{1}{4}\right)}=\frac{2}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{3}{4} + \left( {\frac{1}{2} - \frac{1}{3}} \right) = \frac{9}{{12}} + \left( {\frac{6}{{12}} - \frac{4}{{12}}} \right) = \frac{9}{{12}} + \frac{2}{{12}} = \frac{{11}}{{12}}\)
\(\frac{3}{4} + \frac{1}{2} - \frac{1}{3} = \frac{9}{{12}} + \frac{6}{{12}} - \frac{4}{{12}} = \frac{{15}}{{12}} - \frac{4}{{12}} = \frac{{11}}{{12}}\)
Vậy \(\frac{3}{4} + \left( {\frac{1}{2} - \frac{1}{3}} \right)\) = \(\frac{3}{4} + \frac{1}{2} - \frac{1}{3}\)
b)\(\frac{2}{3} - \left( {\frac{1}{2} + \frac{1}{3}} \right) = \frac{4}{6} - \left( {\frac{3}{6} + \frac{2}{6}} \right) = \frac{4}{6} - \frac{5}{6} = \frac{{ - 1}}{6}\)
\(\frac{2}{3} - \frac{1}{2} - \frac{1}{3} = \frac{4}{6} - \frac{3}{6} - \frac{2}{6} = \frac{1}{6} - \frac{2}{6} = \frac{{ - 1}}{6}\)
Vậy \(\frac{2}{3} - \left( {\frac{1}{2} + \frac{1}{3}} \right)\)=\(\frac{2}{3} - \frac{1}{2} - \frac{1}{3}\).
`#3107`
`a)`
`3/4 + (1/2 - 1/3)`
`= 3/4 + (3/6 - 2/6)`
`= 3/4 + 1/6`
`= 11/12`
`3/4 + 1/2 - 1/3`
`= 9/12 + 6/12 - 4/12`
`= (9 + 6 - 4)/12`
`= 11/12`
Vì `11/12 = 11/12`
`=> 3/4 + (1/2 - 1/3) = 3/4 + 1/2 - 1/3`
`b)`
`2/3 - (1/2 + 1/3)`
`= 2/3 - (3/6 + 2/6)`
`= 2/3 - 5/6`
`= -1/6`
`2/3 - 1/2 - 1/3`
`= 4/6 - 3/6 - 2/6`
`= (4 - 3 - 2)/6`
`= -1/6`
Vì `-1/6 = -1/6`
`=> 2/3 - (1/2 + 1/3) = 2/3 - 1/2 - 1/3`
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=3.\frac{1}{2}\left(2.\frac{1}{3}+\frac{-1}{3}\right)\)
\(A=\frac{3}{2}.\frac{1}{3}=\frac{1}{2}\)
\(B=\frac{-1}{2}\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}\right)\)
\(B=\frac{-1}{2}.\frac{1}{2}=-\frac{1}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(B=\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{2015}}\)
\(\Rightarrow3B=1+\frac{1}{3}+\frac{1}{3^2}+...+\frac{1}{3^{2014}}\)
\(\Rightarrow3B-B=1-\frac{1}{3^{2015}}\)
\(B=\frac{1-\frac{1}{3^{2015}}}{2}\)